2022
DOI: 10.1177/08862605221141869
|View full text |Cite
|
Sign up to set email alerts
|

Sarah Waller’s Help-Seeking Model: Understanding African American Women Intimate Partner Violence Survivors’ Help-seeking Process

Abstract: African American women overwhelmingly experience the poorest outcomes resulting from intimate partner violence (IPV) victimization. Despite theoretical advancements, there remain a paucity of theories that explicate this marginalized population’s comprehensive help-seeking process that includes the domestic violence service provision system and the Black church. We conducted 30 in-depth, semi-structured interviews with women who self-identified as African American. We utilized sensitizing concepts from the Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Despite increased stressors, BIPOC continued to experience structural barriers that precluded their mental health help-seeking efforts. Notably, there is a dearth of access to culturally salient interventions, a paucity of quality of mental healthcare, increases costs for service, and challenges related to health insurance (Burkett, 2017 ; Hankerson et al, 2015 ; Hudson et al, 2018 ; Nicolaidis et al, 2010 ; Redmond et al, 2017 ; Waller et al, 2022a ; Woodward et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite increased stressors, BIPOC continued to experience structural barriers that precluded their mental health help-seeking efforts. Notably, there is a dearth of access to culturally salient interventions, a paucity of quality of mental healthcare, increases costs for service, and challenges related to health insurance (Burkett, 2017 ; Hankerson et al, 2015 ; Hudson et al, 2018 ; Nicolaidis et al, 2010 ; Redmond et al, 2017 ; Waller et al, 2022a ; Woodward et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigating how to assist these students is crucial to prevent adverse health effects and revictimization of IPV (Voth Schrag et al, 2021). Although comparable data of college students are not available in the previous studies, low utilization of formal help-seeking (e.g., health and mental health services) is not only common among Black/African American women IPV survivors (Lacey et al, 2020); these women also face structural barriers in the service systems seeking based on their race, gender, and/or class (e.g., not being believed by the provider, not receiving immediate service; Waller et al, 2022, 2023). These structural barriers also explain a critical gender-based difference in this study, which is that no male participant reported ever seeking help from health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Black/African American women consider many factors in their help-seeking process following IPV victimization. For example, one factor was elevation of IPV (when “the nature, severity, and frequency of the abuse worsened throughout the duration of the relationship,” Waller et al, 2023, p. 7180) so that they finally sought help from police or other formal services (Bent-Goodley et al, 2023; Waller et al, 2023). In other cases, most survivors stopped navigating formal services after experiencing barriers to support from these help-seeking systems (e.g., not being believed by the provider and not receiving immediate service) (Bent-Goodley et al, 2023; Waller et al, 2023).…”
Section: Ipv Help-seeking Behavior Among College Students In Hbcusmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes examining their unique perception of risk, as well as the development of protective behaviors and strategies utilized to escape the cycle of violence. Such analysis can provide valuable insights to enhance their capacities and improve institutional and professional approaches to prevention, protection, and intervention ( Mannell et al, 2014 ; Waller et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%